1988
DOI: 10.1002/rcm.1290020303
|View full text |Cite
|
Sign up to set email alerts
|

Sequential mass spectrometry of saccharides: Identification of 2‐deoxy‐2‐aminohexose stereoisomers in glycoconjugates

Abstract: Mass spectrometric methods for the identification of hexose stereoisomers in glycoconjugates have recently beenThe relative abundance "fingerprints" of the products of collision induced dissocation (CID) were found to be characteristic of the isomeric sugars, and can be used for unambiguous identification of hexose residues in complex molecules. Sequential collision mass spectrometry experiments (MSlMS and MSIMSIMS) were shown to be useful for investigation of the CID reactions of the hexose stereoisomers.3Mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…M211 to an M109 fragment is not observed in MS/MS/ MS experiments (Table 2), and consequently the abundance of Ac24 is taken to be low, and approximate 96% = a(Ac246) + ~(Ac346) 4% = a(Ac234) + a(Ac236) (from 3b) (7) abundances for the predominant species calculated A simple structure b, (Ac46) is inconsistent with rea-(from 3b) (8) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…M211 to an M109 fragment is not observed in MS/MS/ MS experiments (Table 2), and consequently the abundance of Ac24 is taken to be low, and approximate 96% = a(Ac246) + ~(Ac346) 4% = a(Ac234) + a(Ac236) (from 3b) (7) abundances for the predominant species calculated A simple structure b, (Ac46) is inconsistent with rea-(from 3b) (8) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Mass spectrometry specifically with fast atom bombardment (FAB) and liquid secondary ion mass spectrometry (LSIMS) ionization methods have been extensively used to analyze oligosaccharides. The application and limitations of these two similar techniques are well-known and have been illustrated in several review and key articles. Their major limitation is the relatively poor detection limit. Laser desorption, with and without, matrix has been more recently developed but has been used already with great success to analyze carbohydrate structures.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) spectroscopy can give very detailed structural information, but interpretation of the data for complex oligosaccharides is not trivial, and milligram quantities of pure material are often needed for complex two-dimensional experiments Electrospray ionization (ESI) is another ionization technique amenable to oligosaccharides. Reinhold et al have reported ESI of methylated glycosphingolipids and have successfully carried out collision-induced dissociation (CID) .…”
mentioning
confidence: 99%